Learners’ Perception on Bilingual Approach in an EAP Classroom - Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2018)
First language used as a medium of English instruction has been widely used in countries that teach English as a second or foreign language. It is believed that the use of first language can help learners to have access in learning English, increase the motivaton as well the confidence. The following research is intended to find out the learners’ perception on how Indonesian language is prefereable used in their classroom. The 23 respondents were taken from an EAP classroom whose students majoring System of Information and Technology in Bunda Mulia University, Jakarta. The result shown that the learenrs are mostly used Indonesian when they are having discussion among friends however when they interact with their lecturer they expect to have English in returns. On different setting, the learners also prefer Indonesian language is used when the lecturer explaining vocabulary meaning. The result hopefully may help teachers and educators to see this approach as another alternative teaching aid in order to get a better result in their langauge classroom.Keywords: bilingual teaching, language learning, English in Academic Purpose